Indirect Illocutionary Acts of Interrogative Mood in English Quotes: A Functional Grammar - Dini Sri Istiningdias (Jurnal Politikom Indonesiana, 2017)
Abstract: This thesis is entitled Indirect Illocutionary Acts of Interrogative Mood in English Quotes: A Functional Grammar. The writer analyzes English Quotes which published in Brainy Quotes, Disney Words, and Goodreads based on some aspects of functional grammar. In this research, the analyzes are based on the theory of Functional Grammar proposed by Halliday and Mathiessen (2004) and supported with illocutionary acts theory proposed by Downing and Locke (1992) in Deterding (2001), and speech function theory proposed by Eggins (1994) in Emilia (2014). This research uses a descriptive analysis method. The data source is the English Quotes which published in Brainy Quotes, Disney Words, and Goodreads. The research results described the items of data consisting of fifteen (15) Indirect Illocutionary Acts of Interrogative Mood, include four (4) data of Quotes with Yes/No-Interrogative as a Command/Request, two (2) data of Quotes with Yes/No-Interrogative as an Exclamation, five (5) data of Quotes with Wh-Interrogative as a Command/Request, and four (4) data of Quotes with Wh-Interrogative as an Exclamation